A wide temperature range hydrated eutectic electrolyte and its application in aqueous zinc ion batteries
By designing a hydrated eutectic electrolyte system composed of zinc perchlorate hexahydrate, glycol and indium trichloride solutions, the electrolyte freezing and high-temperature side reaction problems of aqueous zinc ion batteries in wide temperature zone use are solved, and the problem of electrolyte freezing and high-temperature side reactions are achieved. The stable use of the battery from -50°C to 50°C and the electrochemical performance improvement is achieved.
Patent Information
- Application Number
- CN202310842474.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-11
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-07-11
AI Technical Summary
At low temperature, the electrolyte freezes, the capacity is reduced and the battery failure is caused by the slow transmission of ions, the capacity is reduced and the battery is malfunctioned due to the high temperature. At high temperature, the high active water molecules accelerate the growth and side reactions of dendrites, resulting in the failure of the battery, which seriously restricts its in-wide temperature zone. Use under conditions.
A hydrated eutectic electrolyte system consisting of zinc perchlorate hexahydrate, ethylene glycol and indium trichloride solutions was designed. The H2O molecule was restricted through the coordination of H2O molecule with Zn2+ and hydrogen bonding with EG. In the eutectic network, the activity of free water is weakened and the freezing point of the electrolyte is reduced, thereby widening the battery's operating temperature range.
This electrolyte system greatly improves the reversibility of Zn and the life of the aqueous zinc ion battery, maintains electrochemical performance in a wide temperature range from -50℃ to 50℃, inhibits the occurrence of dendrites and side reactions, and prolongs the use of the battery life.
Smart Images

Figure CN116799330B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of aqueous zinc ion batteries, and in particular relates to a wide temperature range hydrated eutectic electrolyte and application thereof in aqueous zinc ion batteries. Background Art
[0002] Nowadays, the development of portable electronics, electric vehicles, and renewable energy has stimulated a huge demand for high-performance energy storage devices. Currently, lithium-ion batteries with high specific energy density and high energy efficiency have powered most energy storage systems, but concerns about their safety, resource limitations, and costs are still increasing. Aqueous zinc-ion batteries (AZIBs) are superior to traditional non-aqueous lithium batteries in terms of environmental friendliness, high safety, and low cost, and are one of the most promising candidate batteries for grid energy storage systems.
[0003] However, water, as the main component of aqueous electrolytes, usually freezes at zero degrees. At low temperatures, frozen electrolytes can lead to slow ion transport, reduced capacity, and battery failure. At high temperatures, highly active water molecules accelerate the growth of dendrites and the occurrence of side reactions, and the components in the electrolyte may thermally decompose under high temperature conditions, ultimately leading to battery failure. These factors severely restrict the use of aqueous zinc-ion batteries under wide temperature conditions.
[0004] Therefore, developing an aqueous zinc-ion battery electrolyte with a wide temperature range is of great significance to promoting the application of aqueous zinc-ion batteries in the field of large-scale energy storage. Summary of the invention
[0005] In view of the problems existing in the above-mentioned prior art, the present invention provides a wide temperature range hydrated eutectic electrolyte and its application in an aqueous zinc ion battery, aiming to broaden the operating temperature range of the aqueous zinc ion battery, improve the electrochemical performance of the battery, and extend the service life of the battery.
[0006] The present invention improves the environment of the zinc negative electrode in the electrolyte by designing a eutectic electrolyte, thereby broadening the operating temperature range of aqueous zinc ion batteries. Here, we designed a eutectic electrolyte composed of hexahydrate zinc perchlorate (Zn(ClO 4 ) 2 6H 2 O), ethylene glycol (EG) and indium chloride solution (InCl 3 ) has expanded the temperature range of aqueous zinc-ion batteries to -50°C to 50°C. This has greatly improved the reversibility of Zn and the life of AZIB. 2 O molecules react with Zn 2+The double interactions such as coordination of H and hydrogen bonding with EG are confined in the eutectic network, which weakens the activity of free water and prolongs the electrochemical window of the hydrated eutectic electrolyte. 2 The hydrogen bond network between O molecules is also destroyed, which lowers the freezing point of the electrolyte. In addition, the molecules in the hydrated eutectic electrolyte will evolve into a zinc-philic-zinc-phobic double interface layer at the zinc electrode interface, which prevents direct contact between the electrolyte and the electrode and promotes the Zn 2+ Rapid transportation at high and low temperatures to achieve uniform zinc deposition broadens the operating temperature range of aqueous zinc-ion batteries, improves the electrochemical performance of the batteries, and extends the battery life.
[0007] The wide temperature range hydrated eutectic electrolyte of the present invention comprises zinc salt, alcohol organic solvent and inorganic additive.
[0008] The zinc salt is zinc perchlorate hexahydrate; the alcohol organic solvent is ethylene glycol; and the inorganic additive is indium trichloride solution.
[0009] The wide temperature range hydrated eutectic electrolyte of the present invention is prepared by the following method:
[0010] First, zinc perchlorate hexahydrate and ethylene glycol are mixed in a certain proportion to form a mixed solution; then an inorganic additive indium trichloride solution is added to the mixed solution, and finally the solution is fully mixed by stirring to obtain a hydrated eutectic electrolyte. Specifically, the steps include:
[0011] Step 1: Weigh 3.724-3.730 g of zinc perchlorate hexahydrate into a beaker, add 1862-5.856 g of ethylene glycol, stir at 50-70°C for 50-80 min until the solution is clear and transparent, and cool to room temperature.
[0012] Step 2: Add 10-30% by volume (the volume of the indium chloride aqueous solution accounts for 10-30% of the total volume of the electrolyte) and a concentration of 0.05-0.5 mol / L of an indium chloride aqueous solution to the mixed solution obtained in step 1, stir for 50-80 minutes at room temperature, and obtain a hydrated eutectic electrolyte after the solution becomes clear and transparent.
[0013] The application of the wide temperature range hydrated eutectic electrolyte of the present invention is to construct an aqueous zinc ion battery with the wide temperature range hydrated eutectic electrolyte. The aqueous zinc ion battery comprises a positive electrode, a negative electrode, a diaphragm and the aqueous zinc ion battery electrolyte. The electrolyte can widen the operating temperature range of the aqueous zinc ion battery.
[0014] The negative electrode is made of zinc sheet or zinc foil with a thickness of 10 to 200 μm.
[0015] The positive electrode active material is polyaniline. The positive electrode material preparation method is: polyaniline, conductive agent Ketjen black and binder polyvinylidene fluoride are dispersed in N-methylpyrrolidone in a certain proportion, mixed and evenly coated on a titanium sheet, and dried to form the positive electrode sheet.
[0016] The mass ratio of the polyaniline, Ketjen black and poly(vinylidene fluoride) is in the range of 8:1:1 to 7:2:1.
[0017] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0018] 1. The present invention synthesizes a hydrated eutectic electrolyte based on the interaction of zinc perchlorate, ethylene glycol and indium trichloride solution. The electrolyte has high ionic conductivity and suitable viscosity. The preparation method is simple, low-cost, safe, green and pollution-free.
[0019] 2. The wide temperature range hydrated eutectic electrolyte of the present invention greatly broadens the operating temperature range of the aqueous zinc ion battery, and can still inhibit dendrite growth at high and low temperatures, greatly extending the service life of the aqueous zinc ion battery under high and low temperature conditions.
[0020] 3. H in the hydrated eutectic electrolyte of the present invention 2 O molecules can react with Zn 2+ The dual effects of coordination and hydrogen bonding with ethylene glycol are confined in the eutectic network. On the one hand, the activity of free water is weakened, expanding the electrochemical window of the mixed hydrated eutectic electrolyte. On the other hand, the hydrogen bonding network between water molecules is destroyed, lowering the freezing point of the electrolyte. In addition, the hydrated eutectic electrolyte can form a zinc-phobic-zinc-philic double interface layer in situ on the surface of the zinc negative electrode, promoting the stability of the zinc anode and the Zn 2+ Rapid transport to achieve uniform zinc deposition.
[0021] 4. The zinc ion battery using the wide temperature range hydrated eutectic electrolyte of the present invention has significantly improved cycle stability at high and low temperatures (-50°C to 50°C), showing more excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Digital photos of the electrolytes of Examples 1 to 6 and Comparative Example 1 at 25° C. and -50° C.;
[0023] Figure 2 This is a comparison chart of long cycles of the symmetrical zinc batteries assembled in Examples 1 and 3 and Comparative Example 1 at 25°C;
[0024] Figure 3 This is a comparison chart of long cycles at 25° C. using the symmetrical zinc batteries assembled in Examples 2 and 4 and Comparative Example 1;
[0025] Figure 4 This is a long cycle comparison chart of the symmetrical zinc batteries assembled using Examples 1, 5, and 6 at 25°C;
[0026] Figure 5 This is a long cycle comparison chart of symmetrical zinc batteries assembled using Examples 1 and 2 and Comparative Example 1 at 50°C;
[0027] Figure 6 This is a long cycle comparison diagram of a symmetrical zinc battery assembled using the electrolyte in Example 1 at -50°C;
[0028] Figure 7 This is a long cycle comparison diagram of a symmetrical zinc battery assembled using the electrolyte in Example 2 at -50°C;
[0029] Figure 8 This is a scanning image of the zinc foil after the battery using the electrolyte in Comparative Example 1 was cycled at 25°C;
[0030] Fig. 9 This is a scan of the zinc foil after the battery using the electrolyte in Example 1 was cycled at 25°C;
[0031] Fig.10 Scanning image of zinc foil after the battery using the electrolyte in Comparative Example 1 was cycled at 50°C;
[0032] Fig.11 This is a scan of the zinc foil after the battery using the electrolyte in Example 1 was cycled at 50°C;
[0033] Fig.12 Scanning image of zinc foil after cycling at -50°C using the electrolyte in Example 1;
[0034] Fig.13 This is a carbon element XPS graph of the zinc foil after cycling using the hydrated eutectic electrolyte described in Example 1;
[0035] Fig.14 This is a chlorine element XPS graph of the zinc foil after cycling using the hydrated eutectic electrolyte described in Example 1;
[0036] Fig.15 This is an XPS graph of the indium element of the zinc foil after cycling using the hydrated eutectic electrolyte described in Example 1;
[0037] Fig.16 It is a long cycle performance diagram of a Zn-PANI full battery assembled using the electrolytes in Example 1 and Comparative Example 1 at 25°C;
[0038] Fig.17 It is a long cycle performance diagram of a Zn-PANI full battery assembled using the electrolytes in Example 1 and Comparative Example 1 at 50°C;
[0039] Fig.18 This is a long cycle performance diagram of the Zn-PANI full battery assembled using the electrolyte in Example 1 at -50°C. DETAILED DESCRIPTION
[0040] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiment.
[0041] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0042] Unless otherwise specified, the reagents and materials used in the following examples can be obtained from commercial sources.
[0043] The battery performance tests in the following embodiments all adopt the Xinwei battery test system. The assembly contents of the Zn-Zn symmetrical battery include: two polished zinc sheets are placed at the positive and negative electrodes respectively, the electrolyte is the wide temperature range hydrated eutectic electrolyte prepared in the following embodiments, the glass fiber is the diaphragm, and the assembly is a 2032 button battery. The assembly contents of the Cu-Zn button battery include: copper foil and zinc foil are used as positive and negative electrodes, the electrolyte is the wide temperature range hydrated eutectic electrolyte prepared in the following embodiments, the glass fiber is the diaphragm, and the assembly is a 2032 button battery. The assembly of the Zn-PANI full battery includes: mixing polyaniline (PANI) positive electrode material, Ketjen black and polyvinylidene fluoride (PVDF) in a mass ratio of 70:20:10 and dissolving them in N-methylpyrrolidone (NMP) solution to prepare a slurry, and then evenly coating it on a titanium sheet to prepare a working electrode, using the electrolyte prepared in the following embodiment and glass fiber as a separator to assemble a 2032 button battery, and the test voltage range is 0.5V-1.6Vvs.Zn / Zn 2+ .
[0044] Embodiment 1:
[0045] Step 1: weigh 3.724 g of zinc perchlorate hexahydrate into a beaker, add 2.483 g of ethylene glycol (the molar ratio of zinc perchlorate:ethylene glycol is 1:4), stir at 60° C. for 60 min until the mixed solution becomes clear and transparent, and then cool to room temperature;
[0046] Step 2: Add 30% by volume and 0.1 mol / L indium chloride solution to the mixed solution of step 1, stir for 60 min at room temperature, and obtain a hydrated eutectic electrolyte after the solution becomes clear and transparent, named ZG-14 / ln-30.
[0047] Embodiment 2:
[0048] Step 1: weigh 3.724 g of zinc perchlorate hexahydrate into a beaker, add 3.72 g of ethylene glycol (the molar ratio of zinc perchlorate:ethylene glycol is 1:6), stir at 60° C. for 60 min until the mixed solution becomes clear and transparent, and then cool to room temperature;
[0049] Step 2: Add 30% by volume and 0.1 mol / L indium chloride solution to the mixed solution of step 1, stir for 60 min at room temperature, and obtain a hydrated eutectic electrolyte after the solution becomes clear and transparent, named ZG-16 / ln-30.
[0050] Embodiment 3:
[0051] Step 1: weigh 3.724 g of zinc perchlorate hexahydrate into a beaker, add 2.483 g of ethylene glycol (the molar ratio of zinc perchlorate:ethylene glycol is 1:4), stir at 60° C. for 60 min until the mixed solution becomes clear and transparent, and then cool to room temperature;
[0052] Step 2: Add 10% by volume and 0.1 mol / L indium chloride solution to the mixed solution of step 1, stir for 60 min at room temperature, and after the solution becomes clear and transparent, obtain a hydrated eutectic electrolyte named ZG-14 / ln-10.
[0053] Embodiment 4:
[0054] Step 1: weigh 3.724 g of zinc perchlorate hexahydrate into a beaker, add 3.72 g of ethylene glycol (the molar ratio of zinc perchlorate:ethylene glycol is 1:6), stir at 60° C. for 60 min until the mixed solution becomes clear and transparent, and then cool to room temperature;
[0055] Step 2: Add 10% by volume and 0.1 mol / L indium chloride solution to the mixed solution of step 1, stir for 60 min at room temperature, and obtain a hydrated eutectic electrolyte after the solution becomes clear and transparent, named ZG-16 / ln-10.
[0056] Embodiment 5:
[0057] Step 1: weigh 3.724 g of zinc perchlorate hexahydrate into a beaker, add 3.72 g of ethylene glycol (the molar ratio of zinc perchlorate:ethylene glycol is 1:4), stir at 60° C. for 60 min until the mixed solution becomes clear and transparent, and then cool to room temperature;
[0058] Step 2: Add 30% by volume and 0.5 mol / L indium chloride solution to the mixed solution of step 1, stir for 60 min at room temperature, and obtain a hydrated eutectic electrolyte after the solution becomes clear and transparent, named ZG-14 / ln-30-0.5M.
[0059] Embodiment 6:
[0060] Step 1: weigh 3.724 g of zinc perchlorate hexahydrate into a beaker, add 3.72 g of ethylene glycol (the molar ratio of zinc perchlorate:ethylene glycol is 1:4), stir at 60° C. for 60 min until the mixed solution becomes clear and transparent, and then cool to room temperature;
[0061] Step 2: Add 30% by volume and 0.5 mol / L indium chloride solution to the mixed solution of step 1, stir for 60 min at room temperature, and after the solution becomes clear and transparent, obtain a hydrated eutectic electrolyte named ZG-14 / ln-30-0.05M. Comparative Example 1:
[0062] Weigh 3.724 g of zinc perchlorate hexahydrate into a beaker, add a small amount of deionized water to dissolve, then transfer to a 5 mL volumetric flask, add water to the scale line, and shake until completely dissolved to obtain a 2 mol / L zinc perchlorate electrolyte (named 2MZC).
[0063] Figure 1 The digital photos of the electrolytes of Examples 1 to 6 of the present invention and Comparative Example 1 at 25°C and -50°C are shown. As can be seen from the figure, Comparative Example 1 is in a frozen state at -50°C, while Examples 1 to 6 of the present invention are all flowing liquids at -50°C.
[0064] Figure 2 The long cycle diagram of the symmetrical zinc battery assembled using the electrolytes of Examples 1, 3 and Comparative Example 1. It can be seen from the figure that, compared with the traditional electrolyte in Comparative Example 1, the hydrated eutectic electrolyte of the present invention greatly prolongs the battery cycle life, wherein the cycle life of the battery assembled using Example 1 is almost 20 times that of the battery assembled using Comparative Example 1; the cycle life of the battery assembled using Example 2 is almost 13 times that of the battery assembled using Comparative Example 1.
[0065] Figure 3 The long cycle diagram of the symmetrical zinc battery assembled using the electrolytes of Examples 2, 4 and Comparative Example 1. It can be seen from the figure that although the cycle performance is reduced by changing the proportion of the eutectic electrolyte, Example 2 still extends the cycle life of the zinc symmetrical battery to 2000 hours, which is almost 13 times that of the electrolyte of Comparative Example 1. And Example 4 still extends the cycle life of the zinc symmetrical battery to about 1300 hours, which is almost 9 times that of the electrolyte of Comparative Example 1.
[0066] Figure 4It is a long cycle diagram of the symmetrical zinc battery assembled using Examples 1, 5, and 6. It can be seen from the figure that the hysteresis voltage of the symmetrical battery can be adjusted by changing the concentration of indium trichloride. Although the hysteresis voltage of ZG-14 / ln-30-0.5M is the lowest, the extended cycle life is shorter than that of indium trichloride of other concentrations. Although the hysteresis voltage of Example 1 is higher than that of Example 5, its cycle time is the longest. It shows that a suitable indium trichloride concentration is important for regulating the overall electrochemical performance of the battery.
[0067] Figure 5 This is a long cycle comparison chart of symmetrical zinc batteries assembled using the electrolytes in Examples 1 and 2 and Comparative Example 1 at 50°C. It can be seen from the figure that even at a high temperature of 50°C, the symmetrical battery assembled using the eutectic electrolyte of Example 1 can still operate normally and can be stably cycled for 2500 hours. The symmetrical battery assembled using Example 2 can also operate normally and can be stably cycled for 1000 hours. However, the symmetrical battery assembled using the electrolyte in Comparative Example 1 can only cycle for about 20 hours at high temperature. This shows that the eutectic electrolyte of the present invention has great tolerance to high temperature environments.
[0068] Figure 6 , 7 They are long cycle diagrams of symmetrical zinc batteries assembled using the electrolytes in Examples 1 and 2 at -50°C, respectively. It can be seen from the figure that even at a low temperature of -50°C, the symmetrical battery assembled with the eutectic electrolyte can still operate normally. Example 1 can stably cycle for 800 hours. Example 2 can stably cycle for 200 hours. This shows that the eutectic electrolyte of the present invention has great tolerance to low temperature environments. Considering the effects of different proportions of eutectic electrolytes on the cycle time of the battery at various temperatures, we believe that the ZG-14 / ln-30 electrolyte can maximize the performance improvement of the battery.
[0069] Figure 8 , 9 The scanning images of the zinc foil after cycling at 25° for the batteries assembled using the electrolytes of Comparative Example 1 and Example 1, respectively. At room temperature, the current density is 1 mA / cm 2 After 100 cycles, the zinc foil after the conventional aqueous electrolyte was circulated had uneven zinc deposition on its surface, and was accompanied by large areas of zinc dendrites and byproducts. However, the battery assembled with the hydrated eutectic electrolyte had uniform zinc deposition on the negative electrode surface, without zinc dendrites and byproducts. This indicates that the hydrated eutectic electrolyte of the present invention can effectively inhibit the generation of byproducts and dendrites.
[0070] Fig.10 , 11The scanned images of the zinc foil after cycling at 50° are respectively shown for the batteries assembled using the electrolytes of Comparative Example 1 and Example 1. Since high temperature accelerates the reaction activity, the side reactions on the surface of the zinc negative electrode are accelerated. When the electrolyte of Comparative Example 1 is used, the dendrite growth on the zinc surface becomes more serious. However, the zinc surface using the hydrated eutectic electrolyte can still maintain a relatively uniform plane. This shows that the hydrated eutectic electrolyte of the present invention can still effectively inhibit the formation of by-products and dendrites at high temperatures.
[0071] Fig.12 This is a scan of a zinc foil after cycling at -50° for a battery assembled using the electrolyte of Example 1. It is obvious from the figure that the zinc surface using the hydrated eutectic electrolyte can still maintain a relatively uniform plane under low temperature conditions. This also means that the hydrated eutectic electrolyte of the present invention can effectively inhibit the occurrence of side reactions such as dendrite growth and by-product formation at different temperatures.
[0072] Fig.13 , Fig.14 , Fig.15 The XPS graphs of carbon, chlorine and indium elements of the zinc foil after the hydrated eutectic electrolyte cycle are shown. The analysis shows that a double-layer interface is formed in situ on the Zn surface. The top layer is composed of an organic Cl-containing alkyl component and an inorganic Zn 5 (OH) 8 Cl 2 ·H 2 O-ZnCO 3 The zinc-phobic layer is composed of two components, and the bottom layer is a zinc-philic layer composed of uniform In metal. The zinc-philic interface reduces the energy barrier of zinc nucleation and induces uniform zinc deposition, while the zinc-philic interface prevents active water from penetrating to the surface of the zinc anode and inhibits side reactions. This zinc-phobic / zinc-philic double-layer interface prevents direct contact between the electrolyte and the electrode and induces uniform zinc deposition, promoting the stability of the zinc anode.
[0073] Fig.16 The electrolytes of Example 1 and Comparative Example 1 are respectively used to compare the cycling performance of aqueous zinc ion batteries at 25°C and a current density of 3A / g. After 2000 cycles at 25°C and 3A / g, the Zn||PANI full battery using ZG-14 / ln-30 can maintain a high specific capacity of 82.7mAh / g, with a capacity retention rate of 81.4%. However, the discharge capacity of the Zn||PANI full battery using 2MZC electrolyte drops rapidly, and the capacity retention rate is ultimately less than 50% after 500 cycles, which is attributed to the continued parasitic reactions and growth of Zn dendrites in the aqueous electrolyte.
[0074] Fig.17The electrolytes of Example 1 and Comparative Example 1 are respectively, and the cycle performance comparison diagram of aqueous zinc ion batteries at 50°C and a current density of 3A / g. The Zn||PANI full battery using ZG-14 / ln-30 electrolyte can still provide a long life of 2000 cycles at 3A / g, and the capacity retention rate is as high as 58.0%. In contrast, the capacity of the battery using 2MZC electrolyte is significantly reduced and eventually fails after 500 cycles. High temperature accelerates the growth of dendrites and the occurrence of side reactions. The components in the electrolyte may thermally decompose in a high temperature environment, eventually leading to battery failure.
[0075] Fig.18 The cycling performance diagram of aqueous zinc-ion batteries at -50°C and a current density of 0.1 A / g for the electrolyte of Example 1. The Zn||PANI full battery of ZG-14 / ln-30 is very stable at -50°C, and the capacity retention rate after 2000 cycles is 93.1%. The AZIB based on ZG-14 / ln-30 exhibits excellent cycling stability in the temperature range of -50°C to 50°C, which is due to the excellent tolerance of the mixed hydrated eutectic electrolyte to ultra-high and ultra-low temperatures.
[0076] In summary, the wide temperature range hydrated eutectic electrolyte prepared by the present invention and its application in aqueous zinc ion batteries can improve the stability and reversibility of aqueous zinc ion batteries in a wide temperature window of -50 to 50°C. The hydrated eutectic electrolyte inhibits side reactions such as dendrites and corrosion by in-situ generation of a double-layer interface and a special eutectic network, thereby extending the service life of aqueous zinc ion batteries in harsh environments and improving the cycle stability of the battery. This is of great significance for the scale-up of aqueous zinc ion batteries.
Claims
1. Application of a wide temperature range hydrated eutectic electrolyte in constructing an aqueous zinc ion battery, characterized in that: The wide temperature range hydrated eutectic electrolyte is prepared by the following steps: Step 1: Weigh zinc perchlorate hexahydrate into a beaker, add ethylene glycol, stir at 50°C to 70°C until the solution becomes clear and transparent, and cool to room temperature; Step 2: adding indium trichloride solution to the mixed solution obtained in step 1, stirring at room temperature until the solution is clear and transparent, to obtain a hydrated eutectic electrolyte; In step 1, the molar ratio of zinc perchlorate hexahydrate to ethylene glycol is in the range of 1:3 to 1:9; In step 2, the concentration of the indium chloride solution is 0.05-0.5 mol / L, and the volume of the added indium chloride solution accounts for 10-30% of the total volume of the electrolyte.
2. The use according to claim 1, characterized in that: The aqueous zinc ion battery comprises a positive electrode, a negative electrode, a separator and the wide temperature range hydrated eutectic electrolyte.
Citation Information
Patent Citations
Aqueous electrolyte for inhibiting zinc dendrites and zinc ion battery
CN116259860A
Novel aqueous zinc ion battery electrolyte and preparation method and application thereof
CN116315159A
Cited By
High-temperature-resistant anhydrous eutectic electrolyte for zinc ion battery as well as preparation method and application of high-temperature-resistant anhydrous eutectic electrolyte
CN121097213A
Magnesium ion hydrated eutectic electrolyte and preparation method and application thereof
CN121885794A